The Concept of Tazkiyatun Nafs by Al-Ghazali and Its Implementation at Pesantren Darut Tasbih Tangerang - Ma'muroh; Abqorina; Amrin (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2024)
Imam Al-Ghazali's concept of Tazkiyatun Nafs, emphasizing self-purification through self-control and spiritual development, is increasingly recognized as a foundational approach for character formation and mental well-being within modern Islamic education. This study aims to analyze the implementation of Tazkiyatun Nafs at Pesantren Darut Tasbih, Tangerang, focusing on three primary stages: self-control, self-development, and self-empowerment. Utilizing a qualitative methodology, data were collected through interviews, observations, and document analysis, engaging pesantren leaders, administrators, and students as key sources of information. The findings indicate that the application of Tazkiyatun Nafs in this pesantren significantly enhances students' spiritual well-being, covering personal, communal, environmental, and transcendental dimensions. Students exhibit improvements in emotional regulation, mental stability, social relationships, and a strengthened spiritual connection with God. The study also identifies three students who required extended periods for recovery and spiritual equilibrium, likely due to complex personal issues impacting their healing process. The implications of this research underscore the importance of developing a structured, adaptable educational model grounded in Tazkiyatun Nafs principles, which could be applied across diverse Islamic educational institutions to integrate spiritual approaches in addressing contemporary mental health challenges. These findings reaffirm the contemporary relevance of Al-Ghazali’s teachings and offer practical insights for pesantren administrators seeking to develop holistic, spirituality-based rehabilitation programs.